In situ X-ray diffraction analysis of strain-induced transformations in Fe- and Co-base hardfacing alloys. (15th March 2015) - Smith, R.T.; Lolla, T.; Gandy, D.; Wu, L.; Faria, G.; Ramirez, A.J.; Babu, S.S.; Anderson, P.M.
Abstract : A cobalt-base alloy and an iron-base hardfacing alloy were characterized by in situ diffraction during tensile testing at room and elevated temperatures. Both alloys showed a transition temperature above which a stress-induced martensite transformation disappears. This transition temperature is high (700–825 °C) for the cobalt-base alloy and low (<350 °C) for the iron-base alloy. These values correlate with the temperatures above which wear resistance is reported to decrease in each alloy.